PENYELESAIAN TINDAK PIDANA UJARAN KEBENCIAN BERBASIS RESTORATIVE JUSTICE DENGAN PENDEKATAN FIQIH ISLAH DAN TEORI KOMPENSASI MARAH (Studi Kasus Ujaran Kebencian Gus Nur terhadap NU) - Muhamad Nasrudin; Ibnu Akbar Maliki (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
Since the ITE Law was enacted, public complaints about hate speech on social media have increased, one of which is the case of Gus Nur's hate speech against NU. In various cases, the process of resolving cases in the Court tends to be protracted and does not provide satisfaction for the parties, due to the monodisciplinary approach to litigation in law. Therefore, a breakthrough is needed so that such cases can be resolved quickly, effectively, and with a win-win solution. This article seeks to examine restorative justice breakthroughs with fiqh islah and psychology tools to resolve hate speech cases. To make it more operational, this article takes the case of Gus Nur vs. NU for analysis. This article is written based on empirical legal research that is qualitative in nature with the approach of sociology and legal psychology. The primary data source is a video entitled “Gus Nur & Refly Harun Part 2: Who is the Ideal President? NU Cultural Or Structural?” on the Munjiat Channel Youtube account. While the secondary sources consist of primary legal materials and secondary legal materials. The primary legal materials are Law No. 19 of 2016 concerning Information and Electronic Transactions and the Decree of the Director General of Badilum of the Supreme Court No. 1691/DJU/SK/PS.00/12/2020 concerning Guidelines for the Implementation of Restorative Justice in General Courts. Secondary legal materials are books and journal articles on restorative justice, fiqh ishlah, and anger compensation theory in psychology. After the data was collected by indirect observation and documentation, then it was analyzed using content analysis. The results showed that psychologically Gus Nur was in a state of anger when he made hate speech, thus opening the possibility that he regretted his words which tended to attack NU. While in the review of fiqh ishlah, the most relevant ta'zir sanctions are warnings and apologizing to the NU kiai he mentioned in the hate speech video. With the character of NU who really respects his kiai, when the kiai apologize to Gus Nur, then NU residents can easily forgive Gus Nur. Meanwhile, the restorative justice strategy in this case can be done by taking penal mediation and name rehabilitation.